BIOCHEMICAL CHARACTERIZATION OF ETHANOLIC CRUDE INK AND MUCUS OF DOLABELLA AURICULARIA, WEDGE SEA HARE (LIGHT FOOT 1786) TUTICORIN COAST - S. Tamil Selvi,; K. Bhanumathi,; M. Nandhini,; G. Sankarapandian, (The Bioscan, 2025)
Significantly, the formative research evaluates the biochemical properties of ethanolic extracts of ink and mucus derived from Dolabella auricularia commonly known as wedge sea hare from Tuticorin coast. The quantitative and qualitative research focussed on concentration of bioactive molecules. The invitro analysis of ink and mucus of D.auricularia exhibited potent biochemical activities. The extracts also demonstrated α-amylase inhibition (ink: 50.41%, mucus: 52.01%), membrane stabilization activity (ink: 36.62%), protein denaturation inhibition (ink: 86.46%, mucus: 91.67%), metal chelation (ink: 83.94%, mucus: 80.31%), and antioxidant activity (ink: 72.22%, mucus: 61.11%). These findings suggest wedge sea hare, Dolabella auricularia as a potential source of therapeutic agents, requiring further investigation to isolate bioactive compounds for pharmaceutical applications.